THE EFFECTIVENESS OF THE PERFORMANCE OF GENERASI PESONA INDONESIA ON TOURISM PROMOTION - Adrian Adiwinata; Ambo Tuwo; Ahmad Bahar (Department of Public Administration, Muhammadiyah University of Makassar, 2020)
Seeing many potentials for marine tourism and tourist visits which tend to fluctuate is certainly necessary to have a good performance effectiveness in promoting tourism. This study aimed to analyze the factors that influence the effectiveness of performance of GenPI of Bulukumba on tourism promotion. This study used a qualitative descriptive approach, tries to describe the existing problems based on data from observations, interview and documentation. The researcher presented the data analysis, the results of the interpretation coming to a conclusion. This study used purposive sampling, namely determining the sample based on certain considerations (key informants), namely three members of GenPI of Bulukumba and fourteen regular informants.The results showed that the Personal factors of GenPI of Bulukumba were considered effective because the management already had good expertise, motivation and commitment. The Leadership factor was considered not good because the direction and support only provided through social media would make emotional and familiarity of the board members not well established. The Team factors was effective because the management of GenPI of Bulukumba had good coordination and cooperation in activities which were proven when Bulukumba Regency received a MURI record. The System factors was already effective because even though GenPI of Bulukumba had many limited facilities and there was no decree, GenPI of Bulukumba made achievements. The Contextual/situational factors, internally was considered not good because of a regulation that required the management to upload the posts of GenPI of Bulukumba which were deemed to violate the management's prerogatives.